Solventes de cola: abuso e efeitos nocivos à saúde Glue solvents: abuse and harmful effects on health - Maria de Fátima Menezes Pedrozo; Maria Elisa Pereira Bastos de Siqueira (Universidade de São Paulo, 1989)
O abuso de solventes de cola no Brasil constitui preocupação crescente frente ao aumento do número de usuários, na maioria crianças e adolescentes de baixo nível sócio-econômico. Objetivou-se apresentar alguns aspectos relativos a este abuso, com ênfase especial aos efeitos nocivos decorrentes da inalação aguda e/ou crônica dos solventes das colas. In Brazil, glue sniffing has been of growing concern due to the increasing number of abusers, most of them children and teen-agers of low socio-economic level. This review article presents some aspects of this kind of abuse, with special emphasis on the deleterious effects of acute and/or chronic solvent inhalation (glue-sniffing).